'Not-so-identical' twins with trisomy 21 and perimembranous ventricular septal defects - Sarosh P Batlivala; Kendra S Courtney; Makram R Ebeid; Aimee S Parnell (KARE Publishing, 2016)
Summary- While trisomy 21 is a common genetic disorder in singletons, the incidence among identical twins is very rare, occurring in approximately 1-2 per 1000 twin gestations. Trisomy 21 is associated with high incidence of congenital heart defects, and commonly occurs with ventricular septal defects (VSDs). Physiologic burden of VSDs depends on prevalence of anatomic and other circulatory factors. A case of identical twins with trisomy 21 and large VSDs is described in the present report. Though genetically identical, phenotypes varied significantly. One twin was managed medically, while the other developed more significant heart failure, requiring operative repair.